1978
DOI: 10.1002/j.1552-4604.1978.tb02428.x
|View full text |Cite
|
Sign up to set email alerts
|

Bioavailability of Oral and Intramuscular Phenobarbital

Abstract: The absorption of phenobarbital was compared in healthy adult subjects after oral and intramuscular therapeutic doses. Serum levels of phenobarbital were determined for 21 days after dosing by means of radioimmunoassay. Serum levels were similar from both dosage routes, with peak levels occurring at 1-3 hours after dosing and then declining slowly with an elimination half-life of about 90 hours. The overall efficiency of phenobarbital absorption from intramuscular doses was approximately 80 per cent of that fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

1979
1979
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(17 citation statements)
references
References 13 publications
0
17
0
Order By: Relevance
“…A recent brief clinical report indicated significantly different plasma phenobarbital concentrations in patients who were receiving 32-mg tablets from two manufacturers (2). However, a bioavailability study of a 30-mg tablet indicated better absorption from the tablet than from an intramuscular dose, which was only 80% absorbed (3). In another study (4) the absolute bioavailability of 60-mg tablets was determined, and the extent of absorption averaged 95%.…”
mentioning
confidence: 99%
“…A recent brief clinical report indicated significantly different plasma phenobarbital concentrations in patients who were receiving 32-mg tablets from two manufacturers (2). However, a bioavailability study of a 30-mg tablet indicated better absorption from the tablet than from an intramuscular dose, which was only 80% absorbed (3). In another study (4) the absolute bioavailability of 60-mg tablets was determined, and the extent of absorption averaged 95%.…”
mentioning
confidence: 99%
“…in the treatment of the epilepsies are adequate to yield detectable and dose-congruent drug plasma con centration levels as early as 30 min after single-dose acute administration [Maynert, 1972;Viswanathan et al, 1978Viswanathan et al, , 1979Sannitaet al, 1980;Meyer et al, 1984], Consistent with the dose-related adsorption of this com pound at therapeutic doses [Lous, 1954;Maynert, 1972], the plasma concentration was found to reach its maxi mum level earlier after 50 mg than after the larger dose; by contrast, the power increase on the fast frequency spectral segment was delayed at the 50-mg dose com pared to the 100-mg administration. Systematic and sig nificant modifications of the quantitative EEG profile (notably increment of the fast frequency activity) could be identified despite the low drug plasma concentration levels and were superimposable to those referred to as typical of barbiturates and related compounds [Lennox et al, 1936;Brazier and Finesinger, 1945;Isbell et al, 1950;Wilder et al, 1955;Essig and Fraser, 1958;Bra zier, 1964;Fink, 1969Fink, , 1978Rosadini and Sannita, 1979;Sato, 1980;Sannita et al, 1980Sannita et al, , 1983.…”
Section: Discussionmentioning
confidence: 99%
“…in the treatment of the epilepsies). Single, oral doses of phéno barbital as low as 30 mg however yield consistent drug plasma concentration levels peaking within 2 h after oral administration [Viswanathan et al, 1978[Viswanathan et al, , 1979Meyer et al, 1984], Consistent with these reports, 100-mg single oral doses of phénobarbital proved effective in inducing a significant increase in fast frequency EEG activity in a quantitative EEG study on volunteers, with a maximum effect about 4 h after administration and a definite cor relation with plasma concentration [Sannita et al, 1980], A study to verify whether small oral doses of phénobar bital can induce modifications of the human quantita tive EEG within a postdrug interval compatible with the kinetics described above [Viswanathan et al, 1978[Viswanathan et al, , 1979Meyer et al, 1984] therefore seems pertinent, and would be suggestive of a rapid transport and early bio availability of long-acting barbiturates to the target brain structures.…”
Section: Introductionmentioning
confidence: 99%
“…The area under the plasma drug concentration-time curve was calculated for the single dose (AUC(0,oo)) and at steady-state (AUC(0,24)) using the linear trapezoidal rule. Clearance (CL) was derived from Dose x F/AUC where bioavailability (F) was assumed to be 1 (Viswanathan et al, 1978;Wilensky et al, 1982). The elimination rate constant (k) was calculated by linear least squares regression analysis of the terminal slope of the log plasma drug concentration-time curve.…”
Section: Studymentioning
confidence: 99%